Optimal charging strategy for plug-in hybrid electric vehicle using evolutionary algorithm - Lee, Clement Yuon Sien (2016)
Plug in Hybrid Electric Vehicle (PHEV) is predicted to increase on the road as for users appreciate the benefits that a PHEV can provide. Every PHEV has a battery storage and needs to be recharged. The increase of charging Plug in Hybrid Electric Vehicle on the distribution system due to the increase in number of PHEV on the road will cause overload in the system. Upon this study, a control charging system is needed to control the charging so that the distribution network is not overloaded. An optimal charging strategy for plug-in hybrid electric vehicle (PHEV) is proposed and developed by using evolutionary algorithm to obtain the most suitable charging condition for each PHEV charging. The charging strategy controls the charging time on the vehicle charging load profile (VCLP). VCLP is developed using MATLAB from the real vehicle travel data from National Household Travel Survey (NHTS). The profile is test on IEEE bus-30 system. The results showed that the developed charging strategy achieved the required battery capacity and has reduced peak load and improved load factor thus reduces impacts on power system networks.